2018
DOI: 10.1108/bepam-09-2017-0070
|View full text |Cite
|
Sign up to set email alerts
|

Labour productivity motivation framework for Iskandar Malaysia

Abstract: Purpose The purpose of this paper is to develop a motivation framework that will enhance labour productivity for Iskandar Malaysia (IM) construction projects. The vision of IM development corridor is to become Southern Peninsular Malaysia’s most developed region by the year 2025. IM cannot realise this foresight without effective labour productivity. Previous studies have reported that the labour productivity of IM construction projects was six times lower than the labour productivity of Singapore construction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…Improving construction workforce experience and skills: Numerous studies encouraged that construction laborers should participate in programs of regular training to learn practical skills and real experience (Alaghbari et al, 2019;Enshassi et al, 2007;Liberda et al, 2003;Mahamid, 2013a;Ohueri et al, 2018). Therefore, the authors highlight construction stakeholders should create programs of workshops and training to enhance the construction laborers' experience and managerial skills of the construction parties (Mahamid et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Improving construction workforce experience and skills: Numerous studies encouraged that construction laborers should participate in programs of regular training to learn practical skills and real experience (Alaghbari et al, 2019;Enshassi et al, 2007;Liberda et al, 2003;Mahamid, 2013a;Ohueri et al, 2018). Therefore, the authors highlight construction stakeholders should create programs of workshops and training to enhance the construction laborers' experience and managerial skills of the construction parties (Mahamid et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Enhancing work motivation of the construction workforce: The studies were conducted by (Doloi, 2007;Ghoddousi et al, 2015;Khan et al, 2011;Zakeri et al, 1997) indicated that it is necessary to promote and reward construction laborers as a way of enhancing motivation and work satisfaction to improve labor productivity in the work environment. Besides, the majority of construction practitioners acknowledged the importance of being recognized for their abilities by being rewarded (Momade & Hainin, 2019;Ohueri et al, 2018). Therefore, construction enterprises should provide rewards as a means of demonstrating appreciation for the employees which shows that the managers valued their tasks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have conducted in adjusting energy data for analyzing energy use in buildings and its relationship with LEED credits' Optimize Energy Performance scores in building energy efficiency [1]. In term of green strategy, the integration of technology (use of building information management tools, sustainable construction materials), organization (formulating, applying, monitoring, and evaluating green action plans), occupants' behaviors (education, encouragements, energy efficiency guide) will significantly reduce energy use of green building in many countries [2]. As for the housing industry (real estate developers), some studies have proven that the industry is not completely employed with the energy-efficiency approaches.…”
Section: Related Studiesmentioning
confidence: 99%
“…Furthermore, while Nyoni and Bonga (2016) suggest that management-related factors could resolve construction labour productivity challenges in Zimbabwe, empirically sought and demographically targeted resolutions are non-existent. This is despite the fact that effective management is a major motivator of enhanced construction workers' productivity (Ohueri et al, 2018).…”
Section: Introductionmentioning
confidence: 99%